Application of Dupont-factor analysis to financial performance and market measurement of the southeast Asian hotel industry - Jiang, Jun (International Journal of Applied Economics, Finance and Accounting, 2023)
The study aimed to explore the critical factors impacting the sustainability and growth of the hotel business in the Southeast Asian market. The study covered observations from the second quarter of 2010 to the first quarter of 2022 quarterly reports of 28 listed hotels out of 85 listed in the Southeast Asia markets. By adopting the Dupont equation’s overall business activities measurement, the study tested industrial growth, instability, and market performance in terms relevant to the operating, investing, and financing activities of hotel companies. It was found that fundamental business activities do explain the growth of the hotel industry, with leverage most significantly impacting industrial growth. Industrial instability and market measurement present weak relevance and irrelevance to fundamental accounting measurements of hotel business activities, respectively.